Investigation of Acceptance Level of Adoption towards Early Contractor Involvement (ECI) in Malaysia Construction Industry - Lai, Mei Hao; Nagapan, Sasitharan (Recent Trends in Civil Engineering and Built Environment, 2022)
Every construction project require a complete and efficient project cycle and management to ensure the project can be under control and reach its goals and Design-Bid-build method (DBB) and Design-Build method (DB) as most common used project delivery system but still has risks that may cause conflict during the project life cycle and lead to time and cost overrun. This study is focus on determine the awareness and acceptance level of adoption towards Early Contractor Involvement (ECI) in construction of Malaysia for both public and private sector of construction industry. A survey has been done with questionnaire distributed to determine the awareness of Malaysia construction industry towards ECI and their acceptance level towards adoption of ECI in Malaysia and quantitative data has been collected. The analysis results shows that only 19.2% of respondents aware about ECI but the other 80.8% never learn about ECI and a majority 51.9% of respondents are willing to accept ECI if it is implemented in Malaysia construction industry. The results shows that ECI is not well promoted in Malaysia yet but the majority of the industry is ready to accept ECI implementation in Malaysia and this study able to benefit in raising more awareness of ECI in Malaysia construction industry towards ECI and enhancing transparency and increase effectiveness of communication between stakeholders if ECI is implemented in Malaysia.